Reflecting on the Value of Community Researchers in Criminal Justice Research Projects - Caroline Doyle; Sophie Yates; Jen Hargrave (Social Sciences, 2022)
While the importance of community researchers has long been acknowledged in disability studies, inclusive research practices such as these are less common in research about another marginalised group: people who are in prison or have spent time in prison. Over the past decade in Australia, the number and rate of people imprisoned has risen rapidly, and recidivism rates remain high, indicating a need for improved services. In this article, we draw on methodological reflections from two case studies on research with marginalised communities, one in disability studies and one in post-prison research. We apply insights from disability research to argue the importance of incorporating community researchers in qualitative research projects seeking to explore the experiences of people involved with the criminal justice system, such as people who have been released from prison.